Gender roles in ruminant disease management in Uganda: Implications for the control of peste des petits ruminants and Rift Valley fever (BUILD) - Namatovu, Jane; Lule, Peter; Campbell, Zoe; Tumusiime, Dan; Bett, Bernard; Roesel, Kristina; Ouma, Emily; Marsy, Asindu; Kiara, Henry Kimathi (2024)
Gender roles in ruminant disease management in Uganda: Implications for the control of peste des petits ruminants and Rift Valley fever: This research study is a subcomponent of a bigger project “Boosting Uganda’s Investments in Livestock Development” (BUILD). The output of the research is expected to inform the development PPR and RVF control strategies and options to support ongoing campaigns to eradicate Peste des petits ruminants (PPR) and zoonotic diseases, especially Rift Valley fever (RVF) in Uganda. This study was qualitative and utilised sex-disaggregated focus group discussions with livestock keepers and 32 key informant interviews to explore influencing factors shaping disease control options taken up by men and women in six districts in the western, northeastern, and eastern regions of Uganda during 2020-2021. 16 FGDs were conducted in the RVF sites and 12 FGDs in the PPR sites. The results could guide government in developing appropriate interventions for controlling PPR and RVF.